An intelligent identification system combining image and DNA sequence methods for fruit flies with economic importance (Diptera: Tephritidae). Issue 7 (19th April 2021) - Wang, Jiangning; Chen, Yingying; Hou, Xinwen; Wang, Yong; Zhou, Libing; Chen, Xiaolin
Abstract: BACKGROUND: Images and DNA sequences are two important methods for identifying fruit fly species. In addition, the identification of insect species complexes is highly problematic when attempting to utilize automatic identification methods in an actual environment. We integrated the image and DNA sequence identification methods into a single system for the first time and explored an open interactive multi‐image comparison function for solving the problem of species complexes. The Automated Fruit Fly Identification System 1.0 (AFIS1.0) was updated to AFIS2.0 by employing different models and developing the system under a novel framework. RESULTS: AFIS2.0 was developed using 83 species belonging to eight genera in the Tephritidae, which includes most pests of this family. The system applies the Mask Region Convolutional Neural Network (Mask R‐CNN) and discriminative deep metric learning (AlexNet based) methods for image identification, integrates Blast+ for DNA sequence comparison and specific weighting for the fusion result. At the species level, the best classification success rate for wing images (as the Top 1 species in the species list of outcomes) reached 90%, and the average classification success rate for wing, thorax, and abdomen images (as the Top 5 species in the species list of outcomes) was 94%. CONCLUSION: AFIS2.0 is more accurate and convenient than AFIS1.0 and can be beneficial for users with or without specific expertise regarding Tephritidae. It also provides a more compact and fluent computer system for fruit fly identification, and can be easily applied in practice. © 2021 Society of Chemical Industry. Abstract : This study integrates image identification and DNA sequence comparison methods into a system for the first time. We included 83 species of Tephritidae and the best classification success rate reached 90%. © 2021 Society of Chemical Industry.